Beyond Protection of Civilians: Peacekeeping, Power, and the Crisis of Human Security in South Sudan - Kester C. Onor; Jennifer C. Ndulue (Universitas Medan Area, 2026)
Humanitarian peacekeeping is recognised as an essential international tool for addressing crises and safeguarding vulnerable populations. However, the effectiveness of peacekeeping operations in promoting human security remains contested, particularly in fragile contexts such as South Sudan. This study examines the role of the United Nations Mission in South Sudan (UNMISS) in advancing human security during the period 2013–2021. This research employs a qualitative descriptive approach, using a systematic literature review, drawing on policy documents, humanitarian reports, United Nations publications, and credible secondary data sources. Data were analysed through thematic analysis to identify patterns related to civilian protection and human security outcomes. The Fiduciary Theory of Humanitarian Intervention guides the study’s evaluation of UNMISS’s performance. The findings indicate that UNMISS made measurable contributions to civilian protection, particularly through the establishment of Protection of Civilians (PoC) sites, which, at their peak, sheltered over 200,000 internally displaced persons and reduced their immediate exposure to violence. However, the mission’s overall effectiveness in promoting sustainable human security remained limited due to ongoing armed conflict, weak state institutions, and restricted operational capacity.